TRANSFORMASI NOVEL DANUR 2 MADDAH KARYA RISA SARASWATI KE FILM DANUR 2 MADDAH KARYA AWI SURYADI (KAJIAN EKRANISASI) - A. Asnawi Saputra; Nensilianti Nensilianti; Suarni Syam Saguni (20-87-2496)
Transformation of Novel Danur 2 Maddah by Risa Saraswati into Danur 2 Maddah by Awi Suryadi (Study of Ecranization). This study aims to describe the form of ecranization that experiences shrinking, adding, and changing variations in the categories of the intrinsic elements of the plot, characters, and settings in the transformation of Risa Saraswati's Danur 2 Maddah novel into Awi Suryadi's Danur 2 Maddah film. The research method used is descriptive qualitative. The data sources of this research are Danur 2 Maddah novel by Risa Saraswati and Danur 2 Maddah by Awi Suryadi. Data obtained by reading techniques, note-taking techniques, and documenting techniques. The data were obtained by using quotations (words, phrases, clauses, or sentences) so that it was concluded that the ekranization process occurred because of elements that were deemed unimportant and impossible to visualize, consideration of duration, and consideration of commercial aspects.